The Influence of Principal Pedagogical Competence and School Culture on Student Character Development in Madrasah - Juminah, Juminah; Lian, Bukman; Putra, Alhadi Yan (IKIP Siliwangi, 2023)
The school culture of Madrasah Ibtidaiyah is full of character development, and the role of the Principal as an educator with Pedagogical Competence is predicted to be able to develop students' character significantly. This study aims to prove the influence of the Principal's pedagogical competence and school culture on students' character development in Madrasah. The research was conducted through quantitative methods. The population and sample of the study were 60 people, taken from the entire madrasa academic community in Plaju District. Analysis of the data used is the Multiple Regression Test. The results showed that the Principal's pedagogical competence and school culture simultaneously significantly affected character development. However, based on the partial analysis, the Principal's pedagogical competence is less influential than the teacher's performance in character development.Â